2021
DOI: 10.3389/fpsyg.2021.647723
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Perception, Presence, and Simulation Sickness—A Comparison of Desktop and Head-Mounted Display for Driving Simulation

Abstract: Driving simulators are becoming increasingly common in driver training and assessment. Since virtual reality is generally regarded as an appropriate environment for measuring risk behavior, simulators are also used to assess hazard perception, which is considered to be one of the most important skills for safe driving. Simulators, which offer challenges that are indeed comparable to driving in real traffic, but at a very low risk of physical injury, have the potential to complement theoretical and practical dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…A strong sense of presence is thought to promote simulator validity [106,107]. Cumulative presence scores showed that overall, the scenarios performed well, as all average scores were equal to or greater than five (the maximum possible score being 7).…”
Section: Presence and Sicknessmentioning
confidence: 96%
“…A strong sense of presence is thought to promote simulator validity [106,107]. Cumulative presence scores showed that overall, the scenarios performed well, as all average scores were equal to or greater than five (the maximum possible score being 7).…”
Section: Presence and Sicknessmentioning
confidence: 96%
“…VR headsets eliminate visibility of the physical reality and enable accurate tracking of an individuals’ head movements. Previous research has, however, demonstrated that a sense of presence can still be achieved with a classical desktop screen setup (e.g., Buttussi & Chittaro, 2018; Kwon et al, 2013; Malone & Brünken, 2021). In terms of plausibility illusion, we argue that vBATon provides individuals with a realistic and plausible VE.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has accelerated the spread of RMTs, and it is clear that they will play an even more important role in diagnostics and treatments in the future. Virtual reality is already part of the gaming industry and will soon become the standard for assessing fitness to drive ( 31 ). Voice features will also gain importance as studies indicate their ability to detect cognitive impairment ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%